Transforming body composition with semaglutide in adults with obesity and type 2 diabetes mellitus - Rodríguez Jiménez, Beatriz; Rodríguez de Vera Gómez, Pablo; Belmonte Lomas, Samuel; Mesa Díaz, Ángel Manuel; Caballero Mateos, Irene; Galán, Irene; Morales Portillo, Cristóbal; Martínez-Brocca, María Asunción (Frontiers in Endocrinology, 2024)
Background: Glucagon-like peptide-1 receptor-agonists (GLP-1ra), such as semaglutide, have emerged as promising treatments, demonstrating sustained weight reduction and metabolic benefits. This study aims to assess the impact of oral and subcutaneous semaglutide on body composition and metabolic parameters in patients with T2DM and obesity.Methods: A 24-week quasi-experimental retrospective study including adults with T2DM and obesity (BMI ≥ 30 kg/m²) who were treated with either daily-oral or weekly-subcutaneous semaglutide. Body composition was measured using bioelectrical impedance analysis, evaluating fat mass, fat-free mass, total body water, skeletal muscle mass, and whole-body phase angle. Analytical parameters included lipid profile and glycaemic control. Statistical analyses were performed using SPSS v.26.Results: Participants (n=88) experienced significant weight loss after treatment with semaglutide (9.5% in subcutaneous, 9.4% in oral, P<0.001). Weight reduction primarily resulted from fat mass reduction without substantial lean mass compromise. Visceral fat area decreased, whiles phaseangle remained stable. Improvements in lipid profiles and glycaemic control were observed, with a decrease in both HbA1c and insulin requirements. Multivariate analysis demonstrated comparable impacts of oral and subcutaneous semaglutide on body composition.Semaglutide, administered orally or subcutaneously, demonstrated positive effects on body composition, metabolic and glycaemic control in patients with T2DM and obesity. This real-world study highlights the potential of bioelectrical impedance analysis in assessing antidiabetic drugs' impact on body composition, providing valuable insights for future research and clinical applications.